Contradições Ambientais Da Noruega E Impactos No Brasil Estudo De Caso Sobre Barcarena-PA - BORGES, Daniela Alves Vieira (Universidade Federal do Tocantins, 2024)
The main objective of this research is to conduct a political analysis of Norway's foreign actions, its companies, and their environmental impacts in Brazil. A case study was conducted on Norsk Hydro's activities in Barcarena, Pará, to identify the contradictions between Norway's environmental foreign policy and the impacts of the international activities of its natural resource companies. The theme was approached